Analisis pencatatan dan pelaporan belanja modal pada Badan Keuangan dan Aset Daerah Kota Manado - Tumboimbela, Meiva Jorjia; Wokas, Heince; Kapojos, Peter (Riset Akuntansi dan Portofolio Investasi, 2025)
This study aims to determine the recording and reporting of capital expenditures at the Regional Finance and Assets Agency in Manado City during the implementation of Permendagri No. 77 of 2020. This kind of research is qualitative descriptive. Based on the results of the research, recording or accounting of capital expenditure at the Regional Finance and Assets Agency in Manado City is an important process in public financial management. Reporting is a form of regional financial accountability. Accountability can be realized in the form of financial statements and activities. Financial statements that include information on capital expenditure reports are reports on the realization of regional revenue and expenditure budgets. The recording of capital expenditure in Manado City BKAD is in accordance with the applicable Minister of Home Affairs. During the implementation of Permendagri No. 77 of 2020, the procedure is stricter and more detailed, discussing capital expenditures and using technology to improve financial accuracy and transparency. Capital expenditure reporting in Manado City BKAD is also in accordance with Permendagri No. 77 of 2020 in the Minister of Home Affairs, where capital expenditure reporting is more structured and technology-based.